IMPACT OF CAPTIVITY ON SOCIAL BAHAVIOUR OF CHIMPANZEE (PAN TROGLODYTES) - B. N. Khan (Journal of Animal and Plant Sciences, 2013)
Chimpanzee is the most intellectual species among the animal kingdom. One-year (2009-2010) study on Chimpanzee was conducted to access the impact of captivity on their social behavior at Lahore Zoo. The group consisted of two pairs; one adult and other sub-adult housed in two separate cages. The data was recorded by instantaneous point-sampling technique to determine the frequency, prevalence and duration of different behaviors including abnormal behaviors, activity level, social behaviors and visitors-oriented behaviors. The findings revealed that Chimpanzees of Lahore Zoo were suffering from low level to high-level abnormal behavior and they also displayed natural behavior patterns like their wild relatives. The observed abnormal behaviors such as clapping, urine drinking, fumble nipple, stereotypical grooming, pacing, hair plucking and spiting were more frequent in adult pair than sub-adult pair. However, social behaviors i.e., social grooming, play, and aggression were frequent in sub-adult pair. The prevalence of visitors-oriented behaviors like affiliative and aggressive behaviours was observed in all Chimps. It was observed that attempt to interact with visitors for food, hand hold and play convert the aggression to affiliative relation. It was concluded the lack of social set up, little chance to adapt associative patterns, small cages in contrast to wild habitat and scheduled diet were the major causes to alter the social behavior of Chimps at Lahore Zoo. It is recommended that these animals should be shifted to newly constructed Chimpanzee Island for their welfare and well-being.
Keywords: captivity stress; behavior pattern; animal welfare; social group